Peran Green Human Resource Management Terhadap Green Service Behavior Dengan Green Psychological Climate Sebagai Pemediasi - Zamzamy, Muhammad Virdaus; Suryani, Tatik (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background- Recently, societies are more concerned about green service behavior and green management for supporting sustainable development. Less research in Indonesia focused on that area even though the government has pushed company to implement eco-management for delivering service. This study aims to examine the effect of Green Human Resource Management on green service and to know farther the role of Green Psychological Climate as the mediator of Green Human Resource Management on Green Service (intra role and extra-role Green Service). Aim- This study aims to examine the effect of Green Human Resource Management on green service behavior (Extra role Green Service Behavior and Intra role Green Service Behavior) and the role of Green Psychological Climate as the mediator on that relationship. Methodology- This research was conducted at PT PELNI Surabaya Branch by using quantitative methods. The research involved 200 employees and ata was analyzed by using SmartPLS. Findings- Green Human Resource Management directly affects Intra role Green Service Behavior, but not effect directly on Extra role Green Service Behavior. Green Psychological Climate has a significant effect on Intra role Green Service Behavior and Extra role Green Service Behavior and as a mediator the relationship between Green Human Resource Management on Intra role Green Service Behavior and Extra role Green Service Behavior. Conclusion- Green Human Resource Management has an important role for enhanching psychological climate and Intra role Green Service Behavior. Green Psychological Climate as mediator between Green Human Resource Management and green service behavior. Research Implication- Company should implement Green Human Resource Management properly and develop psychological climate for boosting Green Service Behavior. Limitations- This study only involved workers at PT PELNI Surabaya Branch so that future researchers should conduct similar research in a wider area for more comprehensive results. Keyword: Green Human Resources Management, Green Psychological Climate, Extra role Green Service Behavior, Intra role Green Service Behavior